Prevalence of diseases caused by Flavobacterium spp. and other opportunistic bacteria in carps of sewage-fed farms in West Bengal, India - Sarker, Sudeshna; Abraham, Thangapalam Jawahar; Patra, Avijit (Journal of Fisheries, 2019)
India is the second largest fish producing nation after China, contributing about 5.68% of the global fish production. The state West Bengal is occupying the second position in freshwater fish production after Andhra Pradesh. Although a number of constraints have been put forth, diseases and poor farm management are some of the most noticeable reasons for the reduced fish production in West Bengal. This study reports the prevalence of diseases caused by Flavobacterium spp. and other opportunistic bacteria in carps of sewage-fed farms in West Bengal. The bacteriological examination of the diseased carps revealed infections with different bacterial species and most of them were opportunistic pathogens. Flavobacteriosis, aeromoniasis, pseudomoniasis and other mixed bacterial infections, as confirmed by conventional biochemical tests and by VITEK 2 Compact system, were noted frequently. Antibiotic sensitivity of the opportunistic bacterial pathogens from the diseased carps indicated that some of these bacterial strains are resistant to potential human medicines like erythromycin, cotrimoxazole, oxytetracycline, nitrofurantoin, etc., which is a serious cause for concern. These results further present the fact that sewage-fed fish farms and the food fish from such systems may pose a serious public health risk from the antibiotic-resistant bacteria, if not handled properly.